NFC-Enabled Far-Field Antenna on PET Flexible Substrate for 3G/4G/LTE Mobile Devices - Bancha Luadang; Arnon Sakonkanapong; Sitthichai Dentri; Rassamitut Pansomboon; Chuwong Phongcharoenpanich (My University, 2019)
This research presents a far-field (FF) antenna with near-field communication (NFC) capability for 3G/4G/LTE mobile devices.The integrated far-and near-field communication (FNFC) antenna was fabricated using conductive silver ink on polyethylene terephthalate (PET) flexible substrate.The FF segment of the antenna is operable in the frequency range of 1.8-2.1 GHz, and the NFC antenna is of dual loop and operable at 13.56 MHz.In the antenna realization, simulations were performed and, to validate, an antenna prototype was fabricated.The experimental results revealed that the FF antenna achieved an impedance bandwidth of 37% (1.52-2.21GHz), given |S 11 | of less than -6 dB, with the minimum and maximum efficiency of 92.1% and 98%.The experimental gains are 1.76-2.08dBi across the target operating frequency band, with near-omnidirectional radiation pattern.The simulation and experimental results are in good agreement.Moreover, the FNFC antenna achieves strong magnetic field distributions in H x , H y , and H z orientations and holds promising potential for 3G/4G/LTE applications.
Keywords: Antenna tuner; Antenna Design and Analysis